Equipe de enfermagem e indicadores de recursos humanos e de infecção relacionada à assistência à saúde – um estudo de caso em uma Unidade de Terapia Intensiva de Belo Horizonte, Minas Gerais - Isabella Moreira Torres (2019)
The purpose of the work is to present the restructuring of the nursing team of an Intensive Care Unit of an Educational Public Hospital from Belo Horizonte and to analyze this impacts in the Human Resources and Infection related to Health Care indicatores. The literature review intend to contextualize intensive care units, since the complexity of the scenario influences how resources (human, material, financial, among others) are inserted, used and managed in these units. In the sequence, it addressed aspects related to the nursing workforce, seeking the possible relationships between nursing human resources and the quality of care in the ICU. The topic of Health Care-Related Infections (IRAS) was presented, and specifically about central venous catheter-related bloodstream infections, because it is one of the outcomes that is related to the quality of nursing care and, finally, pointed out some aspects of Human Resources Management as potential influencers of the quality of care. The investigation approach adopted was the single case study, of a descriptive nature, through semi-structured interviews, documentation analysis and evaluation of the historical series of Human Resources and Health Care Related Infection indicators. The central results indicate that the nursing model purposed, according to the professionals perception, brought about an increase in the care for the patients and in the relation to the IRAS indicators. Although the risk of infection related to the nursing assistance has increased significantly after the change, there was a drastic reduction in the density of vascular access infection associated with the central venous catheter. Regarding human resources, a different impact was observed according to the position: improvement in the nursing technicians and worsening of nurses' indicators after the change. These findings trigger important reflections about the role of Human Resources Management in maintaining the positive care results that were obtained and in the sustainability of the model.